Heat Stress and Plant-Biotic Interactions: Advances and Perspectives - Shelake, Rahul Mahadev; Wagh, Sopan Ganpatrao; Patil, Akshay Milind; Červený, Jan; Waghunde, Rajesh Ramdas; Kim, Jae-Yean (Plants (Basel, Switzerland), 2024)
Climate change presents numerous challenges for agriculture, including frequent events of plant abiotic stresses such as elevated temperatures that lead to heat stress (HS). As the primary driving factor of climate change, HS threatens global food security and biodiversity. In recent years, HS events have negatively impacted plant physiology, reducing plant's ability to maintain disease resistance and resulting in lower crop yields. Plants must adapt their priorities toward defense mechanisms to tolerate stress in challenging environments. Furthermore, selective breeding and long-term domestication for higher yields have made crop varieties vulnerable to multiple stressors, making them more susceptible to frequent HS events. Studies on climate change predict that concurrent HS and biotic stresses will become more frequent and severe in the future, potentially occurring simultaneously or sequentially. While most studies have focused on singular stress effects on plant systems to examine how plants respond to specific stresses, the simultaneous occurrence of HS and biotic stresses pose a growing threat to agricultural productivity. Few studies have explored the interactions between HS and plant-biotic interactions. Here, we aim to shed light on the physiological and molecular effects of HS and biotic factor interactions (bacteria, fungi, oomycetes, nematodes, insect pests, pollinators, weedy species, and parasitic plants), as well as their combined impact on crop growth and yields. We also examine recent advances in designing and developing various strategies to address multi-stress scenarios related to HS and biotic factors.
Keywords: microbiome; plant stress; biotic stress; plant–biotic interactions; climate-resilient crops; climate change; heat stress; plant immunity